((3GdfXGe GdbGfhfj dYbO GdJQNjU GdJLGQj hGdUfGYj (B((3GdaQGfTGjR (B: s (3OQGSI ebGQfI eY ETGQI NGUI Edi GdfXGe GdbGfhfj GdadSWjfj (B/ s - (3QTG EHQGgje YHOGddg YHOGddg s; (3Ndjd acJhQ JGOQS (B: s; (3eMehO SejQ GdTQbGhi (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2012)
(3dbO NUUJ gPg GdQSGdI ai JfGhd ehVhY YbO GdaQGfTGjR (B: (3PGJjI gPg GdXGgQI GdJWhQ GdJGQjNi dgG ai GdOhd GdZQHjI hGdYQHjI (B: (3eaghe gPG GdYbO ai Xd GdJTQjYGJ GdebGQfI (B: (3EHQGe GdYbO (B: (3TQhW GfYbGOg (B: (3eMdg (B: (3BKGQ GfYbGOg (B: (3BKGQ GfbVGFg hGdWHjYI GdbGfhfjI dg (B. (3ceG Je ebGQfI GdYbO HHYV GdYbhO GdeTGHgI heaghe GdefGaSI OhdjG (B: (3CKQ JWHjb GdeGOI (B81 (3h (B82 (3ef (BEC Treaty (3Ydi GJaGbjGJ GdaQGfTGjR hXghQ dhGFM GdEYaGA (B4087/88 (3h (B2790/99 (3GdeJYdbI HJWHjb CMcGe GdeGOI (B81/3(3ef GdeYGgOI hXGgQI GdGSJjQGO GdeJhGRi hYdGbJgG HGdYbO eMd GdOQGSI s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2012.s
(3HHdjhLQGajG(B: (3UaMGJ(B359-373.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3YbO GdJQNjU GdJLGQjs; (3GdaQGfTGjR GdUfGYjs; (3GdaQGfTGjR GdeHGTQs; (3GdJRGe GSJYeGd GdYdGeI GdJLGQjIs; (3GdJYhjVs; (3YbO fbd GdJcfhdhLjGs; (3YbO GdhcGdI GdJLGQjIs; (3CMcGe GdefGaSIs; (3Mbhb GdedcjI GdacQjIs; (3XGgQI GdGSJjQGO GdeJhGRjs; (3YbO GdJQNjU GdJLGQjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2012